2009
DOI: 10.1186/1476-4598-8-132
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous constitutive Src kinase activity promotes B lymphoma survival and growth

Abstract: BackgroundPreviously we have shown that B cell receptor (BCR) expression and B cell receptor signaling pathways are important for the basal growth of B lymphoma cells. In particular we have shown that the activation of Syk, a non-src family protein tyrosine kinase and the mitogen activated protein kinases (MAPK), ERK and JNK that mediate BCR signals are required for the constitutive growth of B lymphoma cells. Since src family protein tyrosine kinases (SFKs) like Lyn are known to be needed for the phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 70 publications
0
36
0
Order By: Relevance
“…[47][48][49] These results are novel findings as we are the first to show that WA inhibits key survival kinases that are required for B cell growth. 2,8 In conclusion, we have proposed a mechanism of action by WA that encompasses the broad range of effects shown in DLBCL. It is clear that WA has anti-cancer activities not only in hematological malignancies but also in many solid tumor models previously described.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[47][48][49] These results are novel findings as we are the first to show that WA inhibits key survival kinases that are required for B cell growth. 2,8 In conclusion, we have proposed a mechanism of action by WA that encompasses the broad range of effects shown in DLBCL. It is clear that WA has anti-cancer activities not only in hematological malignancies but also in many solid tumor models previously described.…”
Section: Discussionmentioning
confidence: 99%
“…8 Therefore, we investigated the effect of WA treatment on the protein activity and expression of Lyn, a known SFK needed for the phosphorylation of the BCR co-receptors. 27 As shown in Figure 5B, there is a dramatic loss of expression of pSrc at late time point treatments with WA.…”
Section: Wa Reduces Expression Of Pro-survival Signals In B Cell Lympmentioning
confidence: 99%
See 2 more Smart Citations
“…8 It has been recently shown that SRC family kinases are hyperactivated in many B lymphoma cell lines and primary lymphoma samples but not in normal B cells. [9][10][11] Moreover, SRC inhibition, mediated by the multitargeted tyrosine kinase inhibitor dasatinib and the SRC inhibitors PP1 (4-amino-5-(4-chlorophenyl)-7-(t-butyl)pyrazolo [3,4-d]pyrimidine) and PP2, induced an antiproliferative effect on diffuse large B-cell lymphoma cell lines. [9][10][11] Although these studies are mostly focused on a different lymphoma type, one includes the BL cell line, BJAB and shows that both PP1 and PP2 have antiproliferative effects on this cell line.…”
Section: Introductionmentioning
confidence: 99%